39.3: Invited Paper: Novel Perspective of Nano‐Material: Exploiting Graphene for Display Application. Issue 1 (June 2015) - Jeong, Yongbin; Lee, Dong Chin; Kim, Hyo-Min; Kim, Jeong-Gi; Kang, Jiyeon; Cho, Sung Hee; Choi, Su Seok; Kim, Jinook; Kim, Chul-Hong; Chae, Gee Sung; Jang, Jin; Kang, In Byeong
Abstract : Graphene nano‐ material was firstly exploited for the possible commercial display applications in terms of transparent electrode layer. The device showed better performance than others ever reported based on newly developed material and processes. We report the device feasibility of transparent electrode in conjunction with the work function modification